1988
DOI: 10.1093/oxfordjournals.jbchem.a122339
|View full text |Cite
|
Sign up to set email alerts
|

Presence of Phosphatidylcholine Hydroperoxide in Human Plasma

Abstract: A chemiluminescence-high performance liquid chromatography (CL-HPLC) system was newly developed and used for the hydroperoxide-specific determination of phosphatidylcholine hydroperoxide (PCOOH) in human plasma. The method involves separation of phosphatidylcholine derivatives from plasma lipids by normal phase HPLC and subsequent detection of hydroperoxide-dependent chemiluminescence (CL) of PCOOH. CL was produced through luminol oxidation during the reaction of the hydroperoxide and cytochrome c-heme. The hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
1

Year Published

1989
1989
2015
2015

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 96 publications
(44 citation statements)
references
References 0 publications
0
43
1
Order By: Relevance
“…We have previously confirmed that higher levels of phospholipid hydroperoxides (PLOOH), the primary oxidation products of phospholipids (PL) (1,2) , accumulate abnormally in the erythrocytes of dementia patients (3) . Such erythrocytes with high levels of lipid hydroperoxides have been postulated to have a decreased ability to transport oxygen to the brain, which may impair blood rheology, thus facilitating dementia (4 -8) .…”
Section: Abstract: Astaxanthin: Phospholipid Hydroperoxides: Erythromentioning
confidence: 88%
“…We have previously confirmed that higher levels of phospholipid hydroperoxides (PLOOH), the primary oxidation products of phospholipids (PL) (1,2) , accumulate abnormally in the erythrocytes of dementia patients (3) . Such erythrocytes with high levels of lipid hydroperoxides have been postulated to have a decreased ability to transport oxygen to the brain, which may impair blood rheology, thus facilitating dementia (4 -8) .…”
Section: Abstract: Astaxanthin: Phospholipid Hydroperoxides: Erythromentioning
confidence: 88%
“…All procedures were conducted according to the manufacturers’ instructions. Phosphatidylcholine hydroperoxide (PCOOH) was measured according to the method of Miyazawa [12]and Miyazawa et al [13]. …”
Section: Methodsmentioning
confidence: 99%
“…Contents of PCOOH and PEOOH in the lipid fraction of erythrocyte membranes were determined by a HPLC-chemiluminescence method (27,31). The lipid fraction was dissolved in 5.0 mL of chloroform/ methanol (2:1, vol/vol) and washed twice with 1 mL of 0.05 M KCl to obtain 3.5 mL of the organic layer.…”
Section: Methodsmentioning
confidence: 99%